FAKTOR-FAKTOR YANG MEMPENGARUHI ETOS KERJA RUMAH TANGGA TANI TRANSMIGRAN LOKAL DILAHAN PESISIR DESA BUGEL KECAMATAN PAJATAN KABUPATEN KULON PROGO - Siti Hamidah; Vandrias D; Ahmad Muchlisin (Jurnal Dinamika Sosial Ekonomi, 2009)
Factors That influence Work Ethos of Local Rasetlement in Coastal Area of Village, Subdistric Panjatan, Regency Progo. Objectives of this research to analyze internal factors (family number of famers, age of paterfamilias, education of of paterfamilias and have of water pump) and external factors (intensity training and intensy of elucidation) that influence work ethos of famers and farmer fishermans family and local resettlement bugel. This research using descriptive methode, survey application methode purposive location determination, and sample selection method using Dis Proportional Stratified Random Sampling. The kind of Data is primary and secondary data. Data source obtained from people of local resettlement area of Bugel villase, subdistric Panjatan, Regency Progo, from literatur, and also related instancy. Data collection methode using observation, interview and recording. First objective analyzed with scored technique, whereas second objective with multiple linier regression. Result of the research show that (1) work ethos of famers fishermer family is less than farmer family with total score 28,3 and 32,1 respectively. (2) Factors that influence work ethos farmer and farmer fishermans family are age of farmers, education farmers, intensity of training and education.Keyword:  work ethos, farmers famiy farmer fishermans family